Independent genetic susceptibility to cardiac hypertrophy in inherited hypertension - Innes, B A; McLaughlin, M G; Kapuscinski, M K; Jacob, H J; Harrap, S B (Hypertension (Dallas, Tex. 1979), 1998)
Cardiac hypertrophy is a common but not inevitable complication of hypertension. Variation in heart size in hypertensives may reflect independent genetic susceptibility to cardiac hypertrophy. Using an experimental genetic model, we determined the location of quantitative trait loci responsible for cardiac hypertrophy and/or hypertension. We studied 182 F2 male animals derived from a cross of the spontaneously hypertensive rat and normotensive Donryu rats. Direct mean arterial pressure (MAP) and left ventricular (LV) mass were measured at 20 weeks of age, and DNA was obtained for linkage analysis. The estimated heritability of MAP was 62% and for LV mass expressed per unit of body weight (relative LV mass) was 76%. We used 185 polymorphic markers, with an average intermarker distance of 12.3 centimorgans for a genome-wide scan in a representative subgroup of 46 animals to identify preliminary quantitative trait loci, which were then mapped in all 182 male F2 rats. Two loci showed logarithm of the odds scores of > 4.0. One on chromosome 2, Lvm-1, was linked to relative LV mass but showed no evidence of linkage to MAP. Another locus on chromosome 1, Map-1, was linked to MAP. In the same region, a locus Lvm-2 was linked with relative LV mass. These data indicate the existence of a genetic locus on chromosome 2 of the spontaneously hypertensive rat that affects relative LV mass independently of blood pressure.